2023
DOI: 10.1007/s40688-023-00449-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Mental Health, Technology Use, and Job Satisfaction Among School Psychology Trainers

Abstract: The COVID-19 pandemic threatens to exacerbate the school psychology personnel crisis. There is a dearth of knowledge regarding how the pandemic has impacted school psychology trainers and course delivery. In this national study, 92 school psychology trainers completed an online questionnaire regarding technological instructional changes, job satisfaction, and their own mental health well-being during the pandemic. Findings suggest that during the portion of the pandemic assessed most trainers reported that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…For many people, the sense of threat to their own health and that of their loved ones presented by the pandemic could have intensified feelings of distress, as well as depression and anxiety symptoms [27,28], with young adults being particularly vulnerable [29]. Prolonged exposure to a strong stressor, as in the initial phases of the pandemic, was found to intensify negative emotions such as fear, worry, shame, guilt and nervousness [30,31], particularly in young adults, and this phenomenon has been increasingly studied [32][33][34]. The psychological consequences of the pandemic may well persist for many years in this group, who did not manage to acquire adaptive coping strategies before the outbreak [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…For many people, the sense of threat to their own health and that of their loved ones presented by the pandemic could have intensified feelings of distress, as well as depression and anxiety symptoms [27,28], with young adults being particularly vulnerable [29]. Prolonged exposure to a strong stressor, as in the initial phases of the pandemic, was found to intensify negative emotions such as fear, worry, shame, guilt and nervousness [30,31], particularly in young adults, and this phenomenon has been increasingly studied [32][33][34]. The psychological consequences of the pandemic may well persist for many years in this group, who did not manage to acquire adaptive coping strategies before the outbreak [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, among a sample of teachers, Metrailer and Clark (2022) reported elevated levels of occupational stress and stress associated with COVID-19-related social distancing behaviors were associated with decreases in perceptions of school climate. Finally, Bocanegra et al (2023) reported that, like their k-12 counterparts, school psychology training programs underwent significant changes as they moved from in-person to remote, online instruction. Among their sample of trainers of school psychologists, the accompanying stressors associated with such swift and profound organizational changes were associated with reports of decreased job satisfaction.…”
mentioning
confidence: 99%